Pengembangan Wisata Grojogan Londo melalui Lagu Kreasi sebagai Media Promosi - Mardianto, M. Fariz Fadillah; Pusporani, Elly; Amelia, Dita; Rani, Lina Nugraha; Siregar, Naufal Ramadhan Al Akhwal; Simamora, Antonio Nikolas Manuel Bonar (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Tourism villages are a form of implementation of community-based and sustainable tourism development. Grojogan Londo Tourism has its signature song entitled "Grojogan Londo" by Sodiq New Monata and has been watched 6,230 times on YouTube. In addition, there is a song composed by the Statistics Assisted Village Program Team at the University of Airlangga entitled “Ayang Londo”. Therefore, this study aims to measure respondents' assessment of the two Grojogan Londo Tourism promotional songs. Data was obtained through an online survey using Google Forms with 117 respondents and then analyzed descriptively, correlationally and comparatively. The method used is descriptive statistics, Rank Spearman correlation test, and Mann-Whitney test. The data support the hypothesis that the respondents' interest in the songs "Grojogan Londo" and "Ayang Londo" is different. In addition, 41.9% of respondents believe that music-based promotional media can influence tourists' interest in traveling to certain areas. Therefore, Grojogan Londo tourism promotion songs must be promoted more aggressively through various social media channels which are currently popular among the public, especially the millennial generation. This research contributes to expanding the literature and increasing knowledge about marketing media through songs and their influence on tourist interest which needs to be done as an effort to evaluate tourism development.